HUBUNGAN KECEMASAN DENGAN KESIAPAN MENGIKUTI UJI KOMPETENSI PADA MAHASISWA PROFESI NERS DI SEKOLAH TINGGI ILMU KESEHATAN PASAPUA AMBON - Nastain Pattimura; Isabela Latuheru; Novita Lenony Ruhukael (Pasapua Health Journal, 2022)
Introduction: Anxiety is a condition that makes nursing professional students at STIKES Pasapua Ambon feel uneasy, worried, afraid and tense so that it can affect their readiness to face the competency test. the results of interviews conducted with a small number of Nursing Profession students at the Pasapua Ambon High School of Health Sciences, they said that they were afraid and anxious about facing the Competency Test because they were afraid of failing and not passing. But there are also those who say that they are not too worried about facing the Competency Test because they are confident in their abilities, plus their preparation is quite good because they have studied and practiced the Competency Test questions before. Method: The author uses this research method using a descriptive method correlation with the cross sectional approach data was collected from respondents using a questionnaire sheet via google form. The research sample of 28 respondents was obtained using the Accidental Sampling technique. Results: Of the 28 respondents aged professional students, the most vulnerable were the ages of 23 – 30 years 12 respondents (42.9%), the sex of the nursing profession students is mostly female, 20 respondents (71.4%), most of the nursing profession students do not experience anxiety and are ready to take the competency test as many as 26 respondents (92, 9%) and those who experienced anxiety and were not ready to take the competency test were 2 respondents (7.1%). Conclusion: From the results of data analysis using the chi square statistical test, the p value is obtained value 0.003, thus the p value <0.05, then the hypothesis Ha is accepted and it can be concluded that there is a relationship between anxiety and readiness to take the competency test in nursing professional students at the Pasapua Ambon High School of Health Sciences.Suggestion: it is suggested to institutions that the results of this research can be used as a source of information and professional knowledge as well as for future researchers is expected to be more optimal so that it becomes a comparison with the results of this study.